RNA polymerase II pausing during development. - Gaertner, B.; Zeitlinger, J. (Development, 2014)
The rapid expansion of genomics methods has enabled developmental biologists to address fundamental questions of developmental gene regulation on a genome-wide scale. These efforts have demonstrated that transcription of developmental control genes by RNA polymerase II (Pol II) is commonly regulated at the transition to productive elongation, resulting in the promoter-proximal accumulation of transcriptionally engaged but paused Pol II prior to gene induction. Here we review the mechanisms and possible functions of Pol II pausing and their implications for development.